Nutritive evaluation and dry matter degradability of broiler litter based diets in West African dwarf sheep (2005)
Broiler litter (BL), an animal waste has great potential to reduce the cost of feeding and consequently the cost of production in ruminants. This study was designed to determine the nutritiue value and dry matter (DM) degradability of BL based diets using rumen cannulated West African Dwarf (WAD) sheep. The chemical composition of the BL showed that it contain 84.1% dry matter (DM); 23.5% crude protein (CP); 2.8% ether extract (FE); 20.8% acid detergent fibre (ADF); 39.0% neutral detergent fibre (NDF) and 2 1.5% ash. The BL was used to formulate concentrate rations at graded levels of 0% (control), 25%, 50% and 75% inclusion as diets A, B, C and D, respectively. Rumen degradation characteristics of the BL-based diets showed significant (P<0.05) differences in all the values obtained. The highest soluble fraction (a) value luos recorded for diet B (35.6%) followed by diet C (34.7%). The potential degradable (a+b) fraction was highest in diet D (82.6%) and least in diet A (control), but there were no significant differences in the ‘a+b’ values of diets B and C. It is concluded that inclusion of BL in the diet of ruminants up to 50% level would give optimum performance in sheep.